La historiografía peruana de la segunda mitad del siglo XIX. Una presentación inicial a través de la obra de José Toribio Polo. - Dager Alva, Joseph (Revista Complutense de Historia de América, 2000)
Using the analysis of Jose Toribio Polo's work as a base, we seek to show that the influence of the positivism was relative and partial in the Peru's historiography of the second half of the nineteenth century. For that, we will try to approach to the main characteristics of the way history work was made at that time. In that measure, we will present a general view of what was published in the four main academic magazines of the moment. Besides, we will study the 1 Deseo expresar mi sincero agradecimiento a la doctora Liliana Regalado de Hurtado, quien me motivó a publicar el presente trabajo. 135 Joseph Dager Alva La historiografía peruana en la segunda mitad del siglo XIX most important historiographical polemics, emphasizing the critic that Polo made to the Manuel Mendiburu's Dictionary. Also, we will give the notion of Polo about history as a discipline, which is a sign that he belonged to a transitional generation of historians, between an amateur history and a more scientific one.
Keywords: Perú; Nineteenth Century; José Toribio Polo; historiography; positivism